Component Identification and Analysis of Vesicular Fluid From Swine Infected by Foot-and-Mouth Disease Virus - Zhang, Ting; Lu, Bingzhou; Yang, Bo; Zhang, Dajun; Shi, Xijuan; Shen, Chaochao; Cui, Huimei; Yuan, Xingguo; Zhao, Dengshuai; Yang, Jinke; Hao, Yu; Chen, Xuehui; et al. (Frontiers in Veterinary Science, 2022)
Foot-and-mouth disease (FMD) is induced by FMD virus (FMDV) and characterized by fever and vesicular (blister-like) lesions. However, the exact composition of the vesicular fluid in pigs infected with FMDV remains unclear. To identify and analyze the components of the vesicular fluid in FMDV-infected domestic pigs, the fluid was collected and subjected to mass spectrometry. Further analyses were conducted using Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genome (KEGG), and protein–protein interaction (PPI). Quantitative ELISA kit for TNF-α, and IFN-α, IFN-β, IL-6, IL-10, IL-1β, and IFN-γ were used to verify the mass spectrometry results. Results showed that 937 proteins were identified in the vesicular fluid from swine after FMDV infection, and bioinformatics analysis indicated that these proteins are related to the innate immune and inflammation pathways. The levels of cytokines involved in the disease-related pathways, tumor necrosis factors, and IL-6 in the fluid samples were significantly increased. This study identified and analyzed the composition of vesicular fluid in pigs after FMD infection for the first time and provided interesting information that help understand the infection and pathogenesis mechanism of FMD. These information will eventually contribute to the prevention and control of FMD.